2018
DOI: 10.37358/rc.18.7.6390
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Fly Ash as a Raw Cementitious Material for Geopolymer Concrete

Abstract: This paper presents a review on fly ash as prime materials used for geopolymer. Due to its advantages of abundant resources, less in cost, great workability and high physical properties which lead to achieve high mechanical properties. Fly ash is considered as one of the largest generated industrial solid wastes or so-called industrial by products, around the world particularly in China, India and USA. The characteristics of fly ash allow it to be a geotechnical material to produce geopolymer cement or concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…The strength of geopolymers is a critical factor within the building and construction domain. The development of strength in geopolymers strongly depends on the raw materials and the alkali activator solutions [7][8][9][10][11][12][13][14][15][16]. Even though geopolymers with slow strength development generate materials with lower strength, this drawback can be addressed by increasing heat and aging time [17].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of geopolymers is a critical factor within the building and construction domain. The development of strength in geopolymers strongly depends on the raw materials and the alkali activator solutions [7][8][9][10][11][12][13][14][15][16]. Even though geopolymers with slow strength development generate materials with lower strength, this drawback can be addressed by increasing heat and aging time [17].…”
Section: Introductionmentioning
confidence: 99%
“…A simple technique, known as geopolymerization [3], grows in interest in obtaining building materials with properties similar to those based on Portland cement, but using waste as raw material [4]. The final product obtained through geopolymerization is called geopolymer, which can be described as totally inorganic ceramic material based on aluminum and silicone compounds (table 1) [5].…”
mentioning
confidence: 99%
“…However, the specific gravity of FA is lower than PC, which needs to be taken into consideration in the mix proportioning process. Other standards such as the European standard BS EN206 provide some requirements for the use FA in concrete [7,27,62]. Further study has been carried out by Horpibulsuk et al [63] which reported that FA could be considered as a dispersing material, when it is mixed with cement.…”
Section: Addition Of Fa To Cement and Concretementioning
confidence: 99%